Formulation Policy Regarding the Smuggling of Lobster Seeds in Indonesia - Ayu Izza Elvany (University of Jember, 2020)
This paper analyzes how formulation policy of lobster seeds smuggling regulated in Indonesian law to optimize the effectiveness of illegal fishing enforcement, considering penal policy is the basis of criminal law operationalization. This research uses both statute approach and conceptual approach as legal research methods to analyze the issued legal problem. Fishery law in Indonesia regulated in Law No. 45 of 2009 amending Law No. 31 of 2004 concerning Fishery, especially Articles 88 and 16 paragraph (1) which cover the formulation policy of lobster seeds smuggling enforcement. This study will be analyzed into three aspects which are the conduct (the criminal offense), criminal liability, and sentencing system. The result shows that law enforcement regarding the smuggling of lobster seeds in Indonesia is ineffective due to the nonexistence of corporate criminal liability in the fishery law and its sentencing system is lack of both the specific minimum penalty regulation and the penal measures as criminal punishment. However, the draft of the fishery law has already set corporate criminal liability; hence it also regulates the penal measures, in the form of secondary sanctions. Nevertheless, instead of enacting the specific minimum penalty, the draft only determined the maximum penalty as well. Keywords: Formulation Policy, Fishery Law, Lobster Seeds Smuggling.